Teachers' Strategies in Developing Early Childhood Social Skills Through Play Activities - Novi Nurliani; Nur Fadhilah; Nurlailah; Maswati (CV. Edujavare Publishing, 2026)
This study aims to describe teacher strategies in developing social skills of early childhood through play activities at RA Sonec Al Malik, Pinrang Regency, and to identify the obstacles faced by teachers in their implementation. Social skills represent a fundamental developmental aspect that needs to be stimulated from an early age, particularly through play-based activities appropriate to children's developmental characteristics. This study employed a descriptive qualitative approach with pedagogical and psychological perspectives. Data were collected through participatory observation, in-depth interviews, and documentation involving teachers and the school principal of RA Sonec Al Malik. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results indicate that teachers implement various strategies including role play, cooperative activities, structured group games, and open communication with parents. Obstacles encountered include differences in children's character and lack of home environmental support. This study concludes that well-planned and collaborative play strategies between teachers and parents can significantly optimize the development of social skills in early childhood.